Dampak Bermain Game Online Free Fire Terhadap Kepribadian Sosial Anak-Anak Di Desa Lahumbo Kecamatan Tilamuta Kabupaten Boalemo - Rahman, Riski; Djaafar, Lucyane; Mozin, Nopiana (Innovative: Journal Of Social Science Research, 2024)
Research to determine the impact of playing free fire online games on social personality in children in Lahumbo Village, Tilamuta District, Boalemo Regency. This study uses a descriptive research type with a qualitative approach. The location of this research was conducted in Lahumbo Village, Tilamuta District, Boalemo Regency, with data sources obtained from several informants such as village officials, parents, and children in Lahumbo Village. Data collection was carried out using observation, interview and documentation methods. Researchers act as information diggers with the aim of obtaining data sources, both primary and secondary. The results of this study explain that the impact of online games on most children in Lahumbo Village has many negative impacts and minimal positive impacts on the sustainability and social institutions of the community, especially children in Lahumbo Village. As a result, many complaints arise from parents who complain about bad attitudes towards their children, such as often being disobedient, lazy to go to school, often going out of the house and not wanting to help their parents at home. Conditions like this are very common among children, because the impact of online games is very real and has a negative impact on society, even though the existence of online games can also be a positive thing if parents pay attention and supervise them, considering that not only a few gamers are able to achieve success in playing games. then the government's efforts made to prevent the impact of online games on children in this case there are two efforts, namely preventive and repressive efforts. This action is taken to minimize the impact of online games, because the increasing popularity of online games can no longer be denied that the impacts caused are not only positive impacts but also more prominent negative impacts from online games. Therefore, by combining preventive and repressive efforts, the government is trying to create a safer environment for children to interact with online games.